2021
DOI: 10.1111/gwat.13092
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Multiwell Aquifer Storage and Recovery Systems for Energy Use and Recovery Efficiency

Abstract: As more aquifer storage and recovery (ASR) systems are employed for management of water resources, the skillful operation of multiwell ASR systems has become very important to improve their performance. In this study, we developed MODFLOW and MT3DMS models to simulate a multiwell ASR system in a synthetic aquifer to assess effects of hydrogeological and operational factors on the performance of the multiwell ASR system. We evaluated a simplified (dual well) ASR system in comparison with complex system (three‐,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…They demonstrated that the recovery efficiency increases sub-linearly with the number of cycles. The sub-linear increase of the recovery efficiency with cycle number was also observed in practice (Bakr et al, 2013;Kastner et al, 2017) and in other numerical studies (Sommer et al, 2013;Zeghici et al, 2015;Lu et al, 2011;Majumdar et al, 2021). These findings in the literature agree with the bounds we derived for the cycle exponent,…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They demonstrated that the recovery efficiency increases sub-linearly with the number of cycles. The sub-linear increase of the recovery efficiency with cycle number was also observed in practice (Bakr et al, 2013;Kastner et al, 2017) and in other numerical studies (Sommer et al, 2013;Zeghici et al, 2015;Lu et al, 2011;Majumdar et al, 2021). These findings in the literature agree with the bounds we derived for the cycle exponent,…”
Section: Discussionsupporting
confidence: 91%
“…Several numerical studies (e.g. Bakker, 2010;Lu et al, 2011;Chen, 2014;Barker et al, 2016;Majumdar et al, 2021) showed that in 2D and with 𝐷 𝑚 = 0, the recovery efficiency can be increased by increasing the injection period, or the injection rate, which agrees with the exponents we found for the geometric dispersion factor 𝐺. The fact that the recovery efficiency increases as 𝑄 or 𝑇 increases for 𝑑 = 2 has also been observed in practice (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found three articles discussing the optimization of ASR systems. To varying degrees, each touched on energy use in ASR facilities [26,30,47]. However, we did not find any articles that analyzed the pairing of energy usage and ASR with observed data from actual sites.…”
Section: Discussionmentioning
confidence: 94%
“…Miotliński et al (2014) used detailed aquifer characterization and transport modeling to maintain acceptable quality of recovered water from a multi-well system consisting of four injection and two production wells completed in a brackish water aquifer in Salisbury, South Australia, for the purpose of storage and recovery of freshwater. Majumdar et al (2021) used the MODFLOW-MT3DMS software combination for optimization of recovery efficiency and energy use in a multi-well ASR system conceived in a synthetic aquifer with the objective of providing guidelines for optimizing performance of the multi-well ASR systems.…”
Section: Previous Studies On Numerical Modeling Of Multi-wellmentioning
confidence: 99%